THE COMPARISON OF INSTAN AND HOMEMADE MP-ASI TO MEET NUTRITIONAL STATUS IN INFANT 6-12 MOUNTH THE NORTH CITY HEALTH CENTER - Risky Setiawati; Titin Dunggio; Niluh Arwati (LP2M Universitas Bina Mandiri Gorontalo, 2024)
THIS RESEARCH aims at investigating the comparison of instan and homemade complementary foods to meet the nutritional status of instan aged 6-12 months in the North City Health Center working area. Instant complementary foods are made based on specific provision set by the world health organization (WHO). The type of research used in this study is comparative research, namely comparing the mean value of child growth given Homemade MP-ASI and Instant MP-ASI. The measuremnt scale used is a ratio scale used determine the comparison of Instan and Homemade MP-Asi this study yses Independet t-test analysis. The findings reveal thathave bean presented, it was found that significance value (2-tailed) was 0,348, which is greater than 0,05. Therefore, it can be conclude that there is no significant difference in the average feeding of isntant and homemade complementary foods.